PENGARUH KOMPENSASI FINANSIAL, KOMPENSASI NON FINANSIAL DAN KOMUNIKASI INTERNAL TERHADAP PRESTASI KERJA PEGAWAI DINAS CIPTA KARYA, PERUMAHAN DAN TATA RUANG PROPINSI SULAWESI TENGAH - Syarief, Moh. (Katalogis, 2014)
Compensation  is  a  very  sensitive issue,  compensation  can  influence people performancewhether increase it or vice versa. Compensation needs a clear mechanism. Communication is an important part of organization; an integrated communication can lead an organization to minimize its risk to the very low level. Communication is needed mostly by every pary and level of organization, because some information may be needed not only by a section but also by other sections in an organization. Good communication practice in an organization may indicate that it has good internal organization relationship. Furthermore this will directly lead to better work performance of an agency. As there are a lot of different thought in an organization, they are needed to be united with organization’s vision and mission to lead the organization into the better future. This research utilizes a multiple regression analysis as a statistical tool to assess each variabel effect. The studyresults conclude the independent variables (compensation and internal communication) both simultaneously and partially influence dependent variabel. (employee’s performance). Meanwhile, compensation has dominant effect on employee’s performance.